Quantitatively probing propensity for structural transitions in engineered virus nanoparticles by single-molecule mechanical analysis. Issue 13 (6th March 2015) - Castellanos, Milagros; Carrillo, Pablo J. P.; Mateu, Mauricio G.
Abstract : In a virus particle, the free energy barrier of an inactivating structural transition is linearly related to mechanical stiffness. Elasticity measurements may be applied for probing conformational dynamics of virus-based nanoparticles. Abstract : Viruses are increasingly being studied from the perspective of fundamental physics at the nanoscale as biologically evolved nanodevices with many technological applications. In viral particles of the minute virus of mice (MVM), folded segments of the single-stranded DNA genome are bound to the capsid inner wall and act as molecular buttresses that increase locally the mechanical stiffness of the particle. We have explored whether a quantitative linkage exists in MVM particles between their DNA-mediated stiffening and impairment of a heat-induced, virus-inactivating structural change. A series of structurally modified virus particles with disrupted capsid–DNA interactions and/or distorted capsid cavities close to the DNA-binding sites were engineered and characterized, both in classic kinetics assays and by single-molecule mechanical analysis using atomic force microscopy. The rate constant of the virus inactivation reaction was found to decrease exponentially with the increase in elastic constant (stiffness) of the regions closer to DNA-binding sites. The application of transition state theory suggests that the height of the free energy barrier of the virus-inactivating structural transition increases linearly with local mechanical stiffness. From a virological perspective, the results indicate that infectious MVM particles may have acquired the biological advantage of increased survival under thermal stress by evolving architectural elements that rigidify the particle and impair non-productive structural changes. From a nanotechnological perspective, this study provides proof of principle that determination of mechanical stiffness and its manipulation by protein engineering may be applied for quantitatively probing and tuning the conformational dynamics of virus-based and other protein-based nanoassemblies.